Proposição de um conjunto de diretrizes para orientar a transição do modelo linear de produção para o modelo circular em empresas de manufatura no Brasil - Bacovis, Márcia Maria Costa (Universidade do Vale do Rio dos Sinos, 2021)
The circular economy (CE) is a smart choice in relation to the traditional production system (extraction, manufacturing, use and disposal), according to the objectives of the production cycles and the industrial ecosystem, aiming to reduce and eliminate material waste. The term and concepts CE are new in academia, especially in Brazil, with the main appearance of research since 2010. This research raised a set of sustainable practices and strategies currently developed in companies, which were integrated into a model five-dimensional conceptual framework for CE as follows: Product Design and Development, Process Design, Circular Flow and Business Model, Transition Enablers. The model has been validated in five high-level manufacturing companies. The research was carried out using exploratory methods with qualitative data sets, and the experimental method chosen was multiple cases. This organization intersects with the objective, which is to propose a set of guidelines and a framework for the EC transition. The results confirmed that high-level manufacturing companies are internalizing CE principles with sustainable practices in internal processes to make them more eco-efficient; the results also confirmed that the adoption of new technologies, network collaboration, partnership with universities, and collaboration with stakeholders and value chain partners are key elements that leverage the transition, with the main driver of CE being the innovation. Companies are innovating in product design and development, production processes, and business models for models that slow down or close the production loop. The work brought academic contributions as it advanced knowledge about the transition to CE, showing that the companies surveyed are achieving positive results and competitive advantage, due to environmental gains. As managerial contributions, the set of guidelines and the proposed framework can help managers in the transition and meet the various SDGs (Goals for Sustainable Development) proposed in the UN 2030 Agenda. Political/governmental implications, study limitations, and suggestions for future research were also identified.
Keywords: Economia circular; Modelo de negócios circular; Design circular; Circular economy; Circular business model; Design circular; ACCNPQ::Engenharias::Engenharia de Produção